PEMANFAATAN KAWASAN HUTAN DLUNDUNG TRAWAS UNTUK MENGEMBANGKAN KOMPETENSI IPA TERPADU GURU MTs - Arief, Suto (Balai Diklat Keagamaan Surabaya, 2019)
This research is based on the weak competence of MTs science teachers in conducting integrated sciencelearning so there is a need for on-site training that provides learning resources for the development ofintegrated science competencies for MTs teachers. The purpose of this study was to determine the potentialof the Dlundung Forest Area as a learning resource for MTs science teachers and to find out the integratedscience competencies of MTs teachers that could be developed in training in the Dlundung Forest Area. Thistype of research includes ideas. Sources of ideas were obtained from literature studies and surveys conductedin the Dlundung Trawas Forest Area. The results of the study are as follows: a) The Dlundung Trawas ForestArea has the potential as a learning resource for the development of integrated science competencies for MTsteachers. The Dlundung waterfall area is equipped with heterogeneous forests, organic farming, rabbit parks,campgrounds, waterfalls and rivers, b) There are many integrated science competencies of MTs teachers thatcan be developed through activities in the Dlundung Forest Area.